Yury Buida and Fyodor Dostoyevsky: Types of Intertextual Connections - SHALAGINA, OLGA VADIMOVNA; PROKHOROVA, TATYANA GENNADYEVNA; SHAMINA, VERA BORISOVNA; BOGDANOVA, OLGA VLADIMIROVNA (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The essay addresses various forms of dialogue with F. M. Dostoevsky in the cycle of stories by Yuri Buida ‘The Osor’ins Chronicles’. The authors show that this dialogue is manifested through intertextual connections, allusions, details, narrative techniques defining the inner subplot of the cycle associated with the types of characters, philosophical problems inherent in Dostoevsky’s works (freedom and lack of freedom, crime and punishment, passion and lust), and also with the prophetic forebodings of the writer. RESUMEN El ensayo aborda diversas formas de diálogo con F. M. Dostoievski en el ciclo de historias de Yuri Buida "The Osor’ins Chronicles". Los autores muestran que este diálogo se manifiesta a través de conexiones intertextuales, alusiones, detalles, técnicas narrativas que definen la trama interna del ciclo asociado con los tipos de personajes, problemas filosóficos inherentes a las obras de Dostoievski (libertad y falta de libertad, crimen y castigo, pasión y lujuria), y también con los presentimientos proféticos del escritor.